2014
DOI: 10.1021/ac5006487
|View full text |Cite
|
Sign up to set email alerts
|

Washing-Free Heterogeneous Immunosensor Using Proximity-Dependent Electron Mediation between an Enzyme Label and an Electrode

Abstract: Washing processes, essential in most heterogeneous labeled assays, have been a big hurdle in simplifying the detection procedure and reducing assay time. Nevertheless, less attention has been paid to washing-free heterogeneous labeled assays. We report a purely washing-free immunosensor that allows fast, sensitive, and single-step detection of prostate-specific antigen in serum with low interference. Proximity-dependent electron mediation of ferrocenemethanol (Fc) between an indium-tin oxide (ITO) electrode an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 24 publications
1
62
0
Order By: Relevance
“…24,25 In recent years, we have shown that electrochemical biosensors using ALP labels combined with indium–tin oxide (ITO) electrodes facilitate high signal-to-background ratios, i.e. , very low detection limits 2528 because ITO electrodes show low and flat capacitive background currents.…”
mentioning
confidence: 99%
“…24,25 In recent years, we have shown that electrochemical biosensors using ALP labels combined with indium–tin oxide (ITO) electrodes facilitate high signal-to-background ratios, i.e. , very low detection limits 2528 because ITO electrodes show low and flat capacitive background currents.…”
mentioning
confidence: 99%
“…The blood sample volumes extracted via this one-touch system were determined by the pre-vacuum PDMS chamber volumes, and successful in vivo blood sampling was demonstrated in a rabbit experiment. The self-powered mechanism, disposability, and simplicity of one-touch operation make this system wellsuited for further integration with other microsystems, such as microfluidic chips, 38,39 biosensors, 40,41 and electrode sensors, 42,43 which may be used to realize a real-time micro total analysis system for POC diagnosis. In vivo blood extraction using the self-powered one-touch blood-extraction system.…”
Section: Discussionmentioning
confidence: 99%
“…The three electrode system consisted of a glassy carbon electrode (GCE, 3 mm in diameter) as the working electrode, a saturated calomel electrode (SCE) as the reference, and a platinum wire as the auxiliary. Impedance measurements were performed by applying an ac voltage of 10 mV amplitude in the 0.01 to 10 5 Hz frequency range in a 5.0 mM K 3 [Fe(CN) 6 6 ] redox probe solution with 0.1 M KCl.…”
Section: Apparatus and Electrodesmentioning
confidence: 99%
“…A number of methods and strategies have been reported for the determination of PSA such as fluorescent labeling [2], chemiluminescence [3,4], enzyme labels [5,6], and gold nanoparticle-and carbon nanotube-based biosensors [7]. As point-of-care systems have being increasingly attracted interest in recent years, electrochemical immunoassay seems to be an excellent candidate for the rapid and inexpensive diagnosis of pathogenic biological species of clinical interest [8].…”
Section: Introductionmentioning
confidence: 99%